The Effect of Battle Rope Training on the Long Throw Ability of Football Athlete - Ghildan Magrisha Siddik; Muhamad Tafaqur; Yudi Nurcahya (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of battle ropes training on the long throw-in ability of football athletes. The study used an experimental method with a one-group pretest-posttest design involving 12 male football athletes from Jasukars FC. The training program was carried out for 16 meetings over four weeks with variations of Power Slams, Double Waves, Jumping Slams, Plank Battle Ropes, and Squat to Waves exercises. Data were collected using the Throw-in Distance Measurement instrument and analyzed through the Shapiro-Wilk normality test and the Paired Sample t-test. The results showed a significant increase in long throw-in ability after being given battle ropes training. This increase was caused by the development of upper body strength, explosive power, and core muscle stability produced through dynamic and isometric contractions during the exercise. These findings reinforce that battle ropes training is able to provide specific motor transfer to throw-in mechanics, thereby increasing throwing efficiency and distance. Thus, battle ropes training is recommended as an effective alternative in developing functional strength and throw-in ability for football athletes.